Just War Pacifism: Must it be a Contradiction in Terms?. (August 2019) - Patterson, Colin
Efforts to resolve the tension within the Christian moral theological tradition between just war theory and pacifism have so far not produced any broadly accepted resolution. Key sticking points lie both in the fact that even a just war typically involves the taking of human life, both combatant and civilian, and that the distinction between intentional and unintentional killing, so important to Christian moral reflection, is difficult to sustain in practice. Yet, with the prospect of the development of effective non-lethal weapons, the path may be opened up to a genuine resolution of the tension. This article describes in general terms the way that such a development might be pursued, but also argues that the use of non-lethal weaponry would necessitate a re-interpretation of warfare as an exercise in a form of international policing. A number of potential criticisms of such a proposal are considered.